Improving Student’s Speaking Skill Using Youtube Video as Media: An Action Research - Anggraini Anggraini (Scope : Journal of English Language Teaching, 2021)
This research is an action research that aims to improve students' speaking skills using Youtube media. Discussing how Youtube as a learning medium can improve students' speaking skills. During the Covid 19 pandemic, formal schools are still carrying out the learning process online and only courses are allowed to study face-to-face because there are fewer students in one class, therefore this research was conducted in the Easy English course. Students' speaking ability on the Easy English course is still low especially at the level of children. English course students have difficulty in speaking skills. The students are bored with the old method of improving their speaking skills. The data were collected through speaking assessment and interviewin classroom action research. The writer used Youtube video and students watched and practiced it. Each class consisted of 7 to 10 students, the writer made three cycles and gave a score for each cycle according to the speaking size. The results of the research point out that the students could improve their speaking skills by using Youtube videos. In the first cycle, the students' average score is 65 points, the second cycle is 75 points, and the last cycle is 85 points.